SOLID STATE CP/MAS 13C NMR OF THE INSOLUBLE ORGANIC MATTER OF THE ORGUEIL AND MURCHISON METEORITES: QUANTITATIVE STUDY - Gardinier A.; Derenne S.; Robert F.; Behar F.; Largeau C.; Maquet J. (My University, 2000)
Solid state CP/MAS 13C nuclear magnetic resonance (NMR) study of the insoluble organic fraction isolated by HF/HCl treatment under an inert atmosphere from the Orgueil and Murchison carbonaceous meteorites is reported. Based on these spectra, eight different types of carbons (aro- and ali-linked CH3, CH2, aliphatic C-linked to heteroelements, protonated and non-protonated aromatic C, carboxyls and carbonyls) were identified, their relative amounts were determined and theoretical NMR-derived H/C atomic ratios were calculated. Comparison of these H/C ratios with those obtained from elemental analysis revealed that a large part of the carbons of the insoluble fraction of both meteorites are not detected by CP/MAS 13C NMR. Taking into account these undetected carbons, the relative abundance of aromatic carbons (as % of the total carbons) was calculated as between 69 and 78% in Orgueil and 61 and 67% in Murchison and thus shown to be much higher than previously thought. In addition, the NMR data allowed to calculate the ratio of non-protonated and protonated aromatic carbons. Based on previous studies on chemical and thermal degradation, the present NMR data were interpreted as reflecting the occurrence of highly substituted rather small aromatic moieties in these insoluble organic materials. Along with FTIR data, NMR results also pointed to a relatively high branching level in the aliphatic chains, especially for Murchison. According to the above results, the insoluble organic matter in these meteorites did not suffer a marked thermal maturation during the late hydrothermalism of the parent body. Its synthesis involved a statistical combination of all the possible bonds between -CH3, -CH2 and -CH radicals, producing both the aliphatic and the aromatic moieties. This model explains not only the chemical features of the chondritic insoluble organic material but also the typical FTIR signature of the interstellar medium. Therefore, organic material found in the interstellar medium and that incorporated in the most primitive objects of the solar system seem to share a common organosynthesis.
Keywords: ORGUEIL METEORITE; MURCHISON METEORITE; NMR SPECTRA; ORGANIC COMPOUNDS; AROMATIC HYDROCARBONS